Effect of temperature on the current (capacitance and conductance)-voltage characteristics of Ti/n-GaAs diode - Ejderha, K.; Duman, S.; Nuhoglu, C.; Urhan, F.; Turut, A. (AIP Publishing, 2014)
In this study, Ti/n-GaAs Schottky barrier diode has been fabricated by DC magnetron sputtering. The current-voltage, capacitance-voltage, and conductance-voltage characteristics of Ti/n-GaAs diode have been investigated in the temperature range of 80-320 K. The ideality factor and barrier height values have been calculated from the forward current-voltage characteristics. The variation of the diode parameters with the sample temperature has been attributed to the presence of the lateral inhomogeneities of the barrier height. The temperature dependent capacitance-voltage characteristics have been measured to calculate the carrier concentration, diffusion potential, barrier height, and temperature coefficient of the barrier height (alpha = -0.65 meV K-1). The fact that the temperature coefficient of the barrier height changes from metal to metal has been ascribed to the chemical nature of the contact metal or metal electronegativity. (C) 2014 AIP Publishing LLC.
Keywords: CURRENT-VOLTAGE CHARACTERISTICS; BARRIER HEIGHT DISTRIBUTION; SCHOTTKY BARRIERS; CAPACITANCE-VOLTAGE; ELECTRON-TRANSPORT; SERIES RESISTANCE; SI; PARAMETERS; INHOMOGENEITY; COEFFICIENT; Physics